2013
DOI: 10.1007/s11095-013-1134-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Cytotoxicity and Cellular Uptake of Anti-cancer Drugs by PDE5 Inhibitors in Lung Cancer Cells

Abstract: Purpose Previous research has led to the recognition of a cGMP signaling pathway governing drug transport. This study is to investigate whether inhibitors of phosphodiesterase type 5 (PDE5), which increase intracellular cGMP levels, modulate the cytotoxicity and uptake of anti-cancer drugs in cancer cells. Methods The experiments were conducted with and without PDE5 inhibitors: dipyridamole, vardenafil, and/or sildenafil. The cytotoxicity of doxorubicin, cisplatin and oxaliplatin was determined in multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Moreover the efficacy of the encapsulated drug even in those cancer cells carrying a genetic alteration associated with an aggressive behavior [ 34 , 35 ] may have an important implication for potential personalized therapeutic approaches. At present, there are some reports which suggest the potential use of PDE5 inhibitors as antineoplastic agents [ 10 , 36 , 37 ], but the possible impact of adverse dose-dependent effects owing to their vasodilatatory action has not yet been investigated. If confirmed even in vivo , such a property of our new formulations which would permit the adoption of a low-dosage regimen of the drugs could help to overcome this fundamental issue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the efficacy of the encapsulated drug even in those cancer cells carrying a genetic alteration associated with an aggressive behavior [ 34 , 35 ] may have an important implication for potential personalized therapeutic approaches. At present, there are some reports which suggest the potential use of PDE5 inhibitors as antineoplastic agents [ 10 , 36 , 37 ], but the possible impact of adverse dose-dependent effects owing to their vasodilatatory action has not yet been investigated. If confirmed even in vivo , such a property of our new formulations which would permit the adoption of a low-dosage regimen of the drugs could help to overcome this fundamental issue.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil, vardenafil and dipyridamole were investigated by Li and Shu [ 40 ] as potential enhancers of response to cytotoxic chemotherapy drugs in the H1915 lung cancer cell line and in a murine model. In vitro results showed that all three drugs tested, (at concentrations: 20 μM vardenafil, 100 μM sildenafil and 20 μM dipyridamole), increased the uptake of doxorubicin and carboplatin.…”
Section: Pre-clinical Evidence In Cancer— In Vitro mentioning
confidence: 99%
“…In orthotopic lung cancer model systems, exisulind in association with docetaxel significantly induced apoptosis, reduced tumor growth and metastasis, and increased survival [ 10 , 205 , 206 ]. PDE5 inhibitors also improved the chemosensitivity of anti-cancer agents by increasing endocytosis-mediated cellular drug uptake in lung cancer cells; for instance, oral administration of the PDE5 inhibitor vardenafil significantly increases the accumulation and enhances the anti-tumor effect of trastuzumab in a xenograft mouse model of lung cancer [ 207 ]. Another study showed that sildenafil was able to enhance the anti-tumor effects of the standard of care drug pemetrexed in NSCLCs.…”
Section: Introductionmentioning
confidence: 99%